2022
DOI: 10.1039/d2ma00776b
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating chemical and electrochemical degradation of lithium germanium thiophosphate and the role of atomic layer deposited protection layers

Abstract: Li10GeP2S12 (LGPS) is a superionic conductor that has an ionic conductivity equivalent to conventional liquid electrolytes (~10-2 S cm-1) and thus shows exceptional potential to fulfill the promise of solid-state...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…We repeated the same lithiation process sequence in the LGPS system as a control for the systems with elastomeric ASEI (Figure S11). Similar to the previous literature, , excess Li atoms break PS 4 3– and GeS 4 4– bonds to form Li–S, Li–P, and Li–Ge, leading to decomposition of solid electrolytes. These results further support our experimental post-cycling XPS results, which showed that LPE is remarkably capable of preventing interface degradation reactions at the LGPS/Li interface.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…We repeated the same lithiation process sequence in the LGPS system as a control for the systems with elastomeric ASEI (Figure S11). Similar to the previous literature, , excess Li atoms break PS 4 3– and GeS 4 4– bonds to form Li–S, Li–P, and Li–Ge, leading to decomposition of solid electrolytes. These results further support our experimental post-cycling XPS results, which showed that LPE is remarkably capable of preventing interface degradation reactions at the LGPS/Li interface.…”
Section: Resultssupporting
confidence: 81%
“…We repeated the same lithiation process sequence in the LGPS system as a control for the systems with elastomeric ASEI (Figure S11). Similar to the previous literature, 26,60 excess Li atoms break PS 4 3− and GeS 4…”
Section: Scanning Electron Microscopy and Energy-dispersive X-ray Spe...supporting
confidence: 88%
See 3 more Smart Citations